Application Of Foam-Mat Drying Technology On Production Of Indo-Pacific Tarpon (Megalops cyprinoides) Flavor Enhancer - Reni Tri Cahyani; Sarita Elda Maudi; Hasmini Hasmini; Laode Muhamad Hazairin Nadia (Universitas Negeri Gorontalo, 2023)
Fish have the potential to be a natural source of flavor. Hence, they can be used as the main ingredient in flavor enhancers. This research examines the characteristics of flavor enhancers made from Indo-pacific tarpon produced using foam-mat drying technology. The formulations were the ratio between the weight of fish fleshes and additives namely 30:70 (A); 40:60 (B); 50:50 (C); 60:40 (D); and 70:30 (E). The test parameters included yield, pH, Maillard reaction product, sensory (preference) and proximate value. The best formulation was based on proximate value. The results showed that the different formulations significantly affected the yield, pH, and Maillard reaction product (p0,05). The lower the fish flesh used in the formulation, the higher the yield and Maillard reaction product, while the pH decreased. The effectiveness index test based on sensory value (preference) showed that the formulation D (60:40) was the best formulation that contained water of 8.49 ± 0.30%; ash of 33.03 ± 0.10%; protein of 29.67 ± 0.26%; total fat of 2.00 ± 0.15% and carbohydrates of 26.74 ± 0.10%.